Inhibitory Effects of Brazilian Propolis on Tumor Promotion in Two-Stage Mouse Skin Carcinogenesis - Ken Yasukawa,; So Yeon Yu,; Shigetoshi Tsutsumi,; Masahiko Kurokawa,; Yong K. Park, (Journal of Pharmacy and Nutrition Sciences, 2012)
Propolis is produced by honeybees and has many biological properties, including immunomodulatory, anti-inflammatory, anti-oxidant, anti-bacterial, anti-viral and anti-cancer actions. Five ethanol extracts of Brazilian propolis were tested for inhibition of 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced inflammation in mice. The ethanol extract of Brazilian propolis AF-08 markedly inhibited TPA-induced inflammatory ear edema in mice. This extract suppressed tumor promotion by TPA following initiation with 7,12-dimethylbenz[a]anthracene (DMBA) in mouse skin. Moronic acid, a major component of Brazilian propolis AF-08, markedly inhibited two-stage carcinogenesis by DMBA plus TPA. These results suggest that Brazilian propolis AF-08 contributes to the prevention of cancer.